A study on the relationship between sex, in studying at home and at dormitory, to academic performance - Lumbre, Randy A. (1998)
Academic performance of randomly selected students was studied. Forty senior students have been grouped according to whether they live at home or in dormitories and were also categorized by their sex. Their GWAs were used as basis as to how far they excel in their academic performance, if they were in two different environments, the home and dormitories. By the use of a 2x2 ANOVA, we tested the significance of the three null hypotheses that sex has no significant effect on academic performance, as well as home and dormitories to academic performance, and their interaction. The findings of this study proved the null hypothesis of no significant difference between male and female on academic performance; and between home-environment and dormitory-environment on academic performance. Being a male or a female, and living in these two environments, in other words, do not assure of an excellence in academic performance.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban.
Keywords: Academic performance; Social science